ANALYSIS OF FACTORS AFFECTING TAX MANAGEMENT WITH EFFECTIVE TAX RATE INDICATORS IN A FOOD AND DRINK COMPANY LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2012 - 2019 - Dilvano, M. Bima Agil; Saragih, Fitriani (International Proceeding of Law and Economic, 2022)
In this study, the problems that occur are the lack of maximum use of effective tax rates, an increase in Debt to Asset Ratio) and low inventory turnover so that the time used to spend inventory is long so that the profit earnedexperienced a decrease in food and beverage companies listed on the Indonesia Stock Exchange and was followed by an increase in tax rates.This study aims to examine and analyze the effect of the Debt to Asset Ratio and inventory turnover on the effective tax rate of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2012 - 2019. The population used in this study were 26 food and beverage companies. beverages listed on the Indonesia Stock Exchange, while the samples taken were 5 food and beverage companies using purposive sampling. This study uses an associative approach. The type of data in this research is quantitative. The data analysis technique in this study is using Descriptive Statistical Analysis, multiple Linear Regression analysis, classical assumption test, hypothesis testing, and Coefficient of Determination with a significance level of 5%. The data processing in this study used the SPSS (Statistics Packcage for the Social Sciences) software program for Windows version 23.00. The results of this study indicate that the Debt to Asset Ratio has a significant effect on the effective tax rate of 4.797 with a significance value of 0.000. Inventory turnover has no significant effect on the effective tax rate of 1.072 with a significance value of 0.291. Debt to Asset Ratio and inventory turnover simultaneously have a significant effect on the effective tax rate of 18.241 with a significance value of 0.000.